Radioprotection of healthy tissue via nanoparticle-delivered mRNA encoding for a damage-suppressor protein found in tardigrades - Kirtane, Ameya R; Bi, Jianling; Rajesh, Netra U; Tang, Chaoyang; Jimenez, Miguel; Witt, Emily; McGovern, Megan K; Cafi, Arielle B; Hatfield, Samual J; Rosenstock, Lauren; Becker, Sarah L; Machado, Nicole; et al. (Nature biomedical engineering, 2025)
Patients undergoing radiation therapy experience debilitating side effects because of toxicity arising from radiation-induced DNA strand breaks in normal peritumoural cells. Here, inspired by the ability of tardigrades to resist extreme radiation through the expression of a damage-suppressor protein that binds to DNA and reduces strand breaks, we show that the local and transient expression of the protein can reduce radiation-induced DNA damage in oral and rectal epithelial tissues (which are commonly affected during radiotherapy for head-and-neck and prostate cancers, respectively). We used ionizable lipid nanoparticles supplemented with biodegradable cationic polymers to enhance the transfection efficiency and delivery of messenger RNA encoding the damage-suppressor protein into buccal and rectal tissues. In mice with orthotopic oral cancer, messenger RNA-based radioprotection of normal tissue preserved the efficacy of radiation therapy. The strategy may be broadly applicable to the protection of healthy tissue from DNA-damaging agents.